Pengaruh Konservatisme Akuntansi Dan Corporate Social Responsibility Disclosure Terhadap Kualitas Laba Melalui Manajemen Laba Sebagai Variabel Intervening Pada Perusahaan Pertambangan Yang Terdaftar Di BEI Periode 2016-2019 - Erni Aprillia Simon; Gemi Ruwanti (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2021)
This research aims to achieve empirical prove at the effect of accounting conservatism and Corporate Social Responsibility Disclosure (CSRD) on quality of earning and to investigate whether accounting conservatism and Corporate Social Responsibility Disclosure (CSRD) affects the quality of earnings through earnings management as an intervening variable in mining companies listed on the Indonesia Stock Exchange in 2017 – 2019. The data of this research was secondary data obtained from Indonesia Stock Exchange Website. The population of this research was 15 Mining Companies listed on the Indonesia Stock Exchange in 2016 - 2019. The amount of the obtained sample was 60 sample. This research used classical assumption test with multicollinearity test, autocorellation test, heteroscedasticity test, and normality test. Whereas, the hypothesis testing was completed using multiple linear regression model with determination test, t test and sobel test. Based on research result, it showed that accounting conservatism partially had significant effect on quality of earning and earning manajemen in mining companies listed on the Indonesia Stock Exchange in 2016 – 2019. Moreover, Corporate Social Responsibility Disclosure (CSRD) partially had no significant effect on quality of earning and earning manajemen in mining companies listed on the Indonesia Stock Exchange in 2016 – 2019. Furthermore, accounting conservatism and Corporate Social Responsibility Disclosure (CSRD) had no significant effect on the quality of earnings through earnings management as an intervening variable.